Systematic Literature Review: Inquiry-Based Approaches and Educational Games in Elementary School Mathematics Learning - Juniarta, I Wayan Dika; Astawa, I Wayan Puja; Sudiarta, I Gusti Putu (Darul Yasin Al Sys, 2025)
Although inquiry-based learning and educational game–based instruction have received increasing attention in prior studies, research specifically examining how both approaches can be systematically integrated to enhance conceptual understanding in elementary mathematics remains limited. This study aims to synthesize empirical evidence on the pedagogical alignment, effectiveness, and implementation challenges of combining guided inquiry and educational games in primary mathematics education. A qualitative systematic literature review (SLR) was conducted using the PRISMA framework, yielding a set of eligible articles selected through predefined inclusion criteria. Data were collected through structured document analysis and examined using thematic analysis to identify recurring patterns and relationships across studies. The findings indicate that guided inquiry and educational games exhibit strong pedagogical compatibility, with game features such as real-time feedback, adaptive challenges, and exploratory simulations reinforcing core inquiry processes. Integrated models were found to improve conceptual understanding, motivation, critical thinking, and problem-solving skills, while key challenges relate to teacher readiness, classroom management constraints, and limited technological access. Theoretically, these results contribute to the development of constructivist and inquiry-based learning frameworks and deepen understanding of how digital tools can support conceptual mathematics learning in early education. The study concludes that integrating guided inquiry with educational games offers a powerful and engaging learning environment for young learners and recommends that educators, curriculum designers, and policymakers adopt evidence-based integration strategies and invest in teacher training and digital infrastructure. The implications of this research include strengthened theoretical foundations for game-supported inquiry learning and practical recommendations for improving elementary mathematics instruction, while also highlighting opportunities for future research on model validation, long-term learning impacts, and culturally responsive game design.